2022
DOI: 10.3389/feduc.2022.890834
|View full text |Cite
|
Sign up to set email alerts
|

L2 Teachers’ Pedagogical Thoughts: Variations Across Teachers With Varying Levels of Grit

Abstract: Teacher pedagogical knowledge base (PKB) has secured a notable position in research on teacher cognition. One obvious gap in this strand of research concerns variations in teachers’ thought processes in relation to individual difference variables despite indications that PKB is likely to differ across individual differences. To fill part of the void, this study investigated how teachers’ PKB—conceptualized as the frequency and dominance of pedagogical thought units/categories—vary as a function of teachers’ le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…They also emphasize the impact of teachers’ role in helping learners manage their emotions to enhance efficacy and grit. This finding is in line with the outcomes of Shabani et al (2022) . They concluded that teacher L2 grit is the product of self-reflection, efficacy skills, and affective evaluation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They also emphasize the impact of teachers’ role in helping learners manage their emotions to enhance efficacy and grit. This finding is in line with the outcomes of Shabani et al (2022) . They concluded that teacher L2 grit is the product of self-reflection, efficacy skills, and affective evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…efficacy and grit. This finding is in line with the outcomes of Shabani et al (2022). They concluded that teacher L2 grit is the product of self-reflection, efficacy skills, and affective evaluation.…”
Section: Discussing the Second Research Questionsupporting
confidence: 77%
See 1 more Smart Citation
“…These are two of the effects that may be ascribed to the teachers. As was seen, tenacious educators devote a lot of time and effort to their work, take satisfaction in their instructional strategies, and accomplish all of this despite the difficulties inherent in their professions [ 24 ]. Even though research on language learners’ grit has been showing promising results over the last several years, very little attention has been paid to language teachers’ L2 grit and its related characteristics.…”
Section: Overviewmentioning
confidence: 99%